(untitled) (Academia Science Repository, 2023)
Neuromuscular diseases are one of the numerous groups of hereditary diseases, characterized by muscle diphunctions, a decrease or loss of control of movements. The occurrence of these diseases is associated with a defect in embryonic development or genetically determined pathology. The purpose of this article is to highlight neuromuscular diseases in a new interpretation and to take measures to prevent it.